Da escola para o trabalho: narrativas de pessoas com deficiências egressas da EJA na Baixada Santista - Lima, Waldísia Rodrigues de (2020)
This research aimed to analyse the process of schooling and transition from school to workplace, according to people with disabilities who graduated from Youth and Adult Education (YAE), in the Baixada Santista Metropolitan Region, and verify the contributions of YAE to their inclusion in the workplace. For this purpose, ten people with disabilities from the YAE participated in the research in at least one of the segments: elementary school I, elementary school II and high school. The research is anchored on the oral history method, through Life History, and the data collection was carried out through individual interviews with unstructured script guided by issues related to life memories, family, schooling, work, wishes and dreams. The analysis of the data was based on the qualitative analysis of the life stories, recorded on video and audio, guided by the content analysis of the interview transcripts, correlating them with the main questions, the problem and research objectives, highlighting the frequent points that emerged from the narratives of the interviews, grouped into categories / subcategories followed by the discussions using content description and the interpretation of the interviewees' notes. The interviews, in addition to obtaining the data, made it possible to hear the voice of people with disabilities, in order to understand what they think and feel about the schooling process at YAE, YAE's contributions to workplace inclusion and the transition from school to the workplace. The results indicate that Youth and Adult Education contributed to inclusion in the workplace, with academic, social and communicational knowledge that allowed them to be protagonists of their history in search of their ideals for a full life in society, in addition to bringing light to various aspects related to the life trajectory in schooling at YAE, in work relationships, in the family, in society; in addition, the stories describe young people and adults who are critical and who seek rights and human dignity. Thus, it is believed that the legitimacy of their voices can contribute to the advancement of research in the area of Special Education, Youth and Adult Education and to the inclusion of disabled people in the workplace and can serve for the elaboration of educational policies aimed at schooling and professionalisation, in addition to public policies aimed at inclusion, permanence, progression and guarantees for right to work.